1997
DOI: 10.1038/sj.bmt.1700674
|View full text |Cite
|
Sign up to set email alerts
|

Fatal interstitial pulmonary disease in a patient with dyskeratosis congenita after allogeneic bone marrow transplantation

Abstract: Summary:infections early after BMT 3 and the late complication of vascular damage which may be caused by hypersensitivity to the conditioning agents 4 or interstitial lung disease. 5 Chronic restrictive lung disease in a 9-year-old boy with dyskeratosis congenita (DC) 7 years after allogeneicObstructive lung disease (OLD) has been described as a serious complication after allogeneic BMT. The developbone marrow transplantation (BMT) is described. When he was 1 year and 10 months old, severe aplastic ment of OLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 1 publication
3
62
0
9
Order By: Relevance
“…Previous reports (Table 3) have described progression of the clinical signs of DKC after transplantation, which was indistinguishable from the natural course of disease. [8][9][10][11][20][21][22][23] In our series, all patients except one received low intensity conditioning regimens. The conditioning protocol was different across different centers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports (Table 3) have described progression of the clinical signs of DKC after transplantation, which was indistinguishable from the natural course of disease. [8][9][10][11][20][21][22][23] In our series, all patients except one received low intensity conditioning regimens. The conditioning protocol was different across different centers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the tolerability of the conditioning regimen is always limited by the increased risk of developing significant tissue injury as a result of irradiation and chemotherapy due to inherited defects in genome maintenance. [18][19][20][21][22][23] This hypersensitivity to irradiation and chemotherapy translated into poor survival of patients after SCT, using conventional myeloabaltive conditioning. 20,21 Short-term transplant-related complications are not uncommonly observed in patients with DKC in the setting of allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with BMF due to DC do not respond to immunosuppressive therapy [45]. They are also at high risk of HSCT-related complications due to underlying pulmonary and liver disease [46][47][48][49][50]. In addition, recent studies have shown individuals can be "silent" carriers of a pathogenic mutation in a DC gene [12].…”
Section: Making the Diagnosismentioning
confidence: 99%
“…HSCT is clearly a life-saving measure, but has substantial risks either from toxicity from radiochemotherapy or immune-related complications. Reported problems include graft failure, GVHD, sepsis, pulmonary fibrosis, cirrhosis, and veno-occlusive disease [49;66], due, in part, to underlying pulmonary and liver disease [46][47][48][49][50]. As a result, long-term survival of patients with DC following HSCT has been very poor [49;66].…”
Section: Medical Management Of Dyskeratosis Congenitamentioning
confidence: 99%